2009
DOI: 10.1103/physrevd.80.123020
|View full text |Cite
|
Sign up to set email alerts
|

New stochastic approach to cumulative weak lensing

Abstract: We study the weak gravitational lensing effects caused by a stochastic distribution of dark matter halos. We develop a simple approach to calculate the magnification probability distribution function which allows us to easily compute the magnitude bias and dispersion for an arbitrary data sample and a given universe model. As an application we consider the effects of single-mass large-scale cosmic inhomogeneities (M $ 10 15 h À1 M ) to the SNe magnitude-redshift relation, and conclude that such structures coul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
80
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 60 publications
7
80
0
Order By: Relevance
“…Previous work has shown that correlated structures influence number and height of peaks by only a few percentage points (Marian et al 2010). Furthermore, assuming a stochastical distribution of halos can lead to accurate predictions of the convergence probability distirbution function (Kainulainen & Marra 2009). One may also notice that halos can overlap in 3D space, and indeed we do not exclude this possibility.…”
Section: Probabilistic Approach: Fast Simulationsmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous work has shown that correlated structures influence number and height of peaks by only a few percentage points (Marian et al 2010). Furthermore, assuming a stochastical distribution of halos can lead to accurate predictions of the convergence probability distirbution function (Kainulainen & Marra 2009). One may also notice that halos can overlap in 3D space, and indeed we do not exclude this possibility.…”
Section: Probabilistic Approach: Fast Simulationsmentioning
confidence: 81%
“…To validate this method and to justify various hypotheses that our model makes, we compare results from our fast simulations to those from N-body runs. This approach is similar to the sGL model of Kainulainen & Marra (2009, 2011a, where they show that the stochastic process provides a quick and accurate way to recover the lensing signal distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The second family consists of analytic predictions (Maturi et al 2010;Fan et al 2010) based on Gaussian random field theory. A third approach has been introduced by Lin & Kilbinger (2015, hereafter Paper I): similar to Kruse & Schneider (1999) and Kainulainen & Marra (2009, 2011a, we propose a stochastic process to predict peak counts by simulating lensing maps from a halo distribution drawn from the mass function.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, one may insert the expressions obtained for A 1 (t) and A 2 (t) into the expression (17) for the exterior pressure p e . Moreover, demanding that the pressure is continuous across the boundary allows one also to derive a form for p b (t).…”
Section: Exterior Regionmentioning
confidence: 99%
“…By observing a source in the exterior region, one would then measure an apparent acceleration of the universe's expansion, but this would be only a local effect. The effects of local inhomogeneities on the apparent acceleration of the universe have been widely studied [13][14][15][16][17], and have been linked with the observations of distant Type-IA supernova. We anticipate that our model may also be useful in such a context, although we leave the investigation of this to future research.…”
Section: Introductionmentioning
confidence: 99%